Saturn's magnetospheric interaction with Titan as defined by Cassini encounters T9 and T18: New results - Sittler Jr., E. C. (2010)
We present new results of Cassini’s T9 flyby with complementary observations from T18. Based on Cassini plasma spectrometer (CAPS) and Cassini magnetometer (MAG), compositional evidence shows the upstream flow for both T9 and T18 appears composed of light ions (H+ and H2 +), with external pressures 30 times lower than that for the earlier TA flyby where heavy ions dominated the magnetospheric plasma. When describing the plasma heating and sputtering of Titan’s atmosphere, T9 and T18 can be considered interactions of low magnetospheric energy input. On the other hand, T5, when heavy ion fluxes are observed to be higher than typical (i.e., TA), represents the limiting case of high magnetospheric energy input to Titan’s upper atmosphere. Anisotropy estimates of the upstream flow are 1oT?/T:o3 and the flow is perpendicular to B, indicative of local picked up ions from Titan’s H and H2 coronae extending to Titan’s Hill sphere radius. Beyond this distance the corona forms a neutral torus that surrounds Saturn. The T9 flyby unexpectedly resulted in observation of two ‘‘wake’’ crossings referred to as Events 1 and 2. Event 2 was evidently caused by draped magnetosphere field lines, which are scavenging pickup ions from Titan’s induced magnetopause boundary with outward flux 2 106 ions/cm2 /s. The composition of this out flow is dominated by H2 + and H+ ions. Ionospheric flow away from Titan with ion flux 7 106 ion/cm2 /s is observed for Event 1. In between Events 1 and 2 are high energy field aligned flows of magnetosphere protons that may have been accelerated by the convective electric field across Titan’s topside ionosphere. T18 observations are much closer to Titan than T9, allowing one to probe this type of interaction down to altitudes 950 km. Comparisons with previously reported hybrid simulations are made.